1993
DOI: 10.5636/jgg.45.1159
|View full text |Cite
|
Sign up to set email alerts
|

Multistation Observations of Pc1-2 ULF Pulsations in the Vicinity of the Polar Cusp.

Abstract: Geomagnetic pulsations with frequencies in the range 0.1-2.5 Hz have been recorded with a six station Antarctic magnetometer array ranging in latitude from -62.3 to -80.6° invariant. The observed spectral characteristics were compared with the cusp and boundary layer locations for selected days in November and December, 1986, and July, 1990, in order to determine wave source regions. Specific pulsation features have been identified with different magnetospheric regions. The cusp is characterised by intense uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…•.•...a aries are of the greatest current interest. Thus we will place our observations in context principally by comparison with the .recent studies of Menk et al [ 1992Menk et al [ , 1993 and Hansen et al…”
Section: In Both Of These Figures Crosses Represent Observed Polewardmentioning
confidence: 82%
See 2 more Smart Citations
“…•.•...a aries are of the greatest current interest. Thus we will place our observations in context principally by comparison with the .recent studies of Menk et al [ 1992Menk et al [ , 1993 and Hansen et al…”
Section: In Both Of These Figures Crosses Represent Observed Polewardmentioning
confidence: 82%
“…Such emissions also often include periodic emissions. Menk et al [1992Menk et al [ , 1993 We used ULF survey plots such as the one in Figure 1, which were routinely produced using data from all stations, to select candidate band-limited pulsations in the appropriate frequency band for HM chorus. In these survey plots power in one component (in this case east/west, or Y) is plotted as a function of universal time using a base 10 logarithmic scale for 10 different frequency bands, whose upper frequency range is shown in the left side of the figure.…”
Section: Event Identification and Sample Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are also supported by a statistical study of DeLauretis et al (1991), who found that the average daytime background spectra at cusp latitudes (Iqualuit, Canada) exhibit p = −(3.47-3.80) over the Pc3 frequency range. As has been emphasized by Menk et al (1993), these values cannot be explained solely by either the KHI, which predicts p = −5/3 (Kolmogoroff's hydrodynamic turbulence) or p = −3 (ion-acoustic turbulence), or the drift wave insta-bility giving p = −5 (D'Angelo, 1973).…”
Section: Separation Of Signal and Noisementioning
confidence: 99%
“…The predominant high‐latitude (L = 6–8) ground ULF signal near local noon is quasi‐structured hydromagnetic chorus/emissions [ Fukunishi et al , 1981; Menk et al , 1993; Anderson et al , 1995]. Since the early 1960s, it has been noted that the ULF waves on the ground near local noon were either turned on or enhanced in association with sudden impulses in the Earth's magnetic field [ Troitskaya , 1961; Heacock and Hessler , 1965; Kokubun and Oguti , 1968; Troitskaya et al , 1968; Hirasawa , 1981].…”
Section: Introductionmentioning
confidence: 99%